Proceedings of the 57th Annual Meeting of the Association for Computational Linguistics: Student Research Workshop 2019
DOI: 10.18653/v1/p19-2059
|View full text |Cite
|
Sign up to set email alerts
|

Annotating and Analyzing Semantic Role of Elementary Units and Relations in Online Persuasive Arguments

Abstract: For analyzing online persuasions, one of the important goals is to semantically understand how people construct comments to persuade others. However, analyzing the semantic role of arguments for online persuasion has been less emphasized. Therefore, in this study, we propose a novel annotation scheme that captures the semantic role of arguments in a popular online persuasion forum, so-called ChangeMyView. Through this study, we have made the following contributions: (i) proposing a scheme that includes five ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…On this data set, Niculae (2018) achieved a maximum F1-score of 0.74 for proposition classification using linear structured SVMs. Egawa, Morio, and Fujita (2019) adjust the annotation scheme of Park and Cardie slightly, replacing reference with rhetorical statement (which implicitly states the subjective value judgment by expressing figurative phrases, emotions, or rhetorical questions) and replacing the relations with the more standard attack and support. This scheme was then used to annotate 345 posts from the ChangeMyView sub-Reddit, 32 resulting in 4,612 proposition classifications and 2,713 relations that were then used in analyzing the semantic role of persuasive arguments.…”
Section: Intrinsic Clausal Propertiesmentioning
confidence: 99%
“…On this data set, Niculae (2018) achieved a maximum F1-score of 0.74 for proposition classification using linear structured SVMs. Egawa, Morio, and Fujita (2019) adjust the annotation scheme of Park and Cardie slightly, replacing reference with rhetorical statement (which implicitly states the subjective value judgment by expressing figurative phrases, emotions, or rhetorical questions) and replacing the relations with the more standard attack and support. This scheme was then used to annotate 345 posts from the ChangeMyView sub-Reddit, 32 resulting in 4,612 proposition classifications and 2,713 relations that were then used in analyzing the semantic role of persuasive arguments.…”
Section: Intrinsic Clausal Propertiesmentioning
confidence: 99%
“…As Lawrence and Reed (2019) state, "one of the challenges faced by current approaches to argument mining is the lack of large quantities of appropriately annotated arguments to serve as training and test data." Since the availability of labeled corpora is crucial for designing, training and evaluating AM algorithms, numerous prior works have dealt with creating annotated data sets, such as the Araucaria corpus (Reed et al, 2008b), the European Court of Human Rights (ECHR) corpus of , the Debatepedia corpus (Cabrio and Villata, 2012), the ChangeMyView corpus (Egawa et al, 2019) or the persuasive essays corpus of Stab and Gurevych (2014a) with 90 essays and the corpus of Stab and Gurevych (2017a) with 402 persuasive student essays. These corpora have been widely used for various AM tasks, such as the identification of argument components (Rooney et al, 2012), corpus wide AM (Ein-Dor et al, 2019) or end-to-end AM (Persing and Ng, 2016).…”
Section: Argument Annotated Corpora and Annotation Schemesmentioning
confidence: 99%
“…To get a better understanding of the persuasiveness of requests on crowdfunding platforms, Yang et al [13] presented a hierarchical neural network in a semi-supervised fashion to make the persuasiveness quantifiable. Egawa et al [14] demonstrated five types of elementary units and two types of relations to characterize persuasive arguments and proposed an annotation scheme to capture the semantic roles of arguments in an online persuasive forum [15,3,4]. Furthermore, Hidey and McKeown [16] proposed a neural model with words, discourse relations, and semantic frames to predict persuasiveness in social media.…”
Section: Related Workmentioning
confidence: 99%